Assessment Supply Chain Performance and Risk of Agricultural Commodities in South of Sulawesi (International Journal of Scientific Research and Management (IJSRM), 2017)
The supply chain of agricultural commodities is very complex, because many actors and activities in the production process. The main actors of supply chain are farmers, then small collectors, large sellers, market traders, retailers and end-use consumers. This study aims to assess the performance and risk of supply chain agricultural commodities in South Sulawesi. The research method used is qualitative descriptive. The results showed that there are four supply chains in vegetable and fruit commodities in South Sulawesi. While the risk of supply chain using five assessments of price changes, shrinking value, market access, weather and infrastructure.